SISTEM INFORMASI TABUNGAN SISWA PADA MI ADI PODAY MENGGUNAKAN PHP DAN MYSQL - Arifin, Miftahul (Journal of Advanced Research in Informatics, 2023)
MI Adi Poday is a primary level educational institution under the auspices of the Ministry of Religious Affairs in Sumenep Regency. The current savings data management system is still done manually, with data recording and storage written in books, and calculations performed using a calculator as a tool. The analysis results indicate that the existing system has shortcomings, particularly in the software component to assist with data management. Therefore, in the design phase, software design was carried out to address the issues arising from the existing system. Based on the implementation and testing results of the designed software, it is shown that the savings data management software is capable of addressing the issues that arise prior to the implementation of the savings data management software.